2008
DOI: 10.1007/s10692-009-9067-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitrogen atoms in forming the carbon structure in the carbonization of polymer composites

Abstract: Data have been used from X-ray photoelectron spectroscopy, small-angle X-ray spectroscopy, nuclear magnetic resonance, IR Fourier spectroscopy, electron spectroscopy, and other current methods for polyacrylonitrile, polypyromellitimide, hydrated cellulose, hard coals, and various model compounds to examine the effects of the nitrogen atoms on carbonization and graphitization. The nitrogen atoms are found to have multiple effects on the thermochemical and thermophysical parameters of the polymer carbonization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Considering that three transition structural have been showed in the DSC curve of gelatin sample, it can be verified that a lot of functional group in the gelatin molecule (carboxylic, amine, alkyl) was changed to alkaline due to temperature increase. The integrity of the triple helix structure was preserved in gelatin sample, since denatured gelatin did not present any thermal transition in the temperature intervals studied [21][22][23]. The SBA-15 addition reduced transition temperature of the composite.…”
Section: Fig 3 Ft-ir Spectra Of Mcg Sample At Different Wave Numbermentioning
confidence: 88%
“…Considering that three transition structural have been showed in the DSC curve of gelatin sample, it can be verified that a lot of functional group in the gelatin molecule (carboxylic, amine, alkyl) was changed to alkaline due to temperature increase. The integrity of the triple helix structure was preserved in gelatin sample, since denatured gelatin did not present any thermal transition in the temperature intervals studied [21][22][23]. The SBA-15 addition reduced transition temperature of the composite.…”
Section: Fig 3 Ft-ir Spectra Of Mcg Sample At Different Wave Numbermentioning
confidence: 88%
“…[28][29][30][31][32][33][34] Under charring conditions, the ve membered hetero rings may rearrange to six membered rings 35 followed by condensation to generate graphene units doped with heteroatoms at the edges and basal planes for stability. [35][36][37] In addition, peripheral oxo groups are introduced at the edges of the graphene layer during carbonization in air. 20 The heteroatoms at the edges or in the basal planes mismatch the standard interlayer spacing in graphite to yield the turbostratic form.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Moreover,d uring the carbonization process, nitrogenc an reduce the carbonizationt emperature of thermally stable carbon materials. [8] In particular,i th as been demonstratedt hat sodium ions can penetrate into carbonm atrixes, and therefore, inducet he realignmento fa morphous carbon and manipulatet he cross-linked network. [9] It is highly desirable to combine thesem eanso fh eteroatom doping and metal sulfide/metallic nanoparticle dopingw ith the molten-salt method towards the development of high-performance anodes forS IBs.…”
Section: Introductionmentioning
confidence: 99%
“…Molten‐salt medium is an efficient way to capture nitrogen during the preparation of carbon nitride . Moreover, during the carbonization process, nitrogen can reduce the carbonization temperature of thermally stable carbon materials . In particular, it has been demonstrated that sodium ions can penetrate into carbon matrixes, and therefore, induce the realignment of amorphous carbon and manipulate the cross‐linked network .…”
Section: Introductionmentioning
confidence: 99%